Modelling bacterial meningitis in the African meningitis belt for the evaluation of preventive vaccination - (:unkn) unknown (My University, 2019)
Pathophysiological mechanisms underlying the seasonal dynamic and epidemic occurrence of bacterial meningitis in the African meningitis belt remain unknown. Regular seasonality (hyperendemicity) is observed for meningococcal and pneumococcal meningitis. Understanding this is critical for better prevention and modelling. The two main hypotheses for hyperendemicity during the dry season imply an increased risk of invasive disease given asymptomatic carriage of meningococci and pneumococci; or an increased transmission of these bacteria from carriers and ill individuals. We developed three mathematical models of seasonal hyperendemicity, featuring one or a combination of the two hypotheses. Models were parameterized based on current knowledge on meningococcal and pneumococcal biology and pathophysiology. We compared the models’ performance in reproducing weekly incidences cases of acute bacterial meningitis reported by health centres in Burkina Faso during 2004–2010, through meningitis surveillance. All models performed well (R2, 0.72, 0.86, 0.87). Seasonal forcing transmission only or and risk of meningitis better captured amplitude of seasonal incidence. However, seasonal forcing transmission alone required a higher constant invasion rate. These results suggest a combination of seasonal changes of the risk of invasive disease and carriage transmission is involved in hyperendemic bacterial meningitis in the African meningitis belt. Consequently, interventions reducing the risk of nasopharyngeal invasion and the bacteria transmission, especially during the dry season are believed to be needed to limit the recurrent seasonality of bacterial meningitis in the meningitis belt.
Keywords: African Research